Core–shell materials bearing iron(ii) carbonyl units and their CO-release via an upconversion process. Issue 41 (27th September 2017) - Ou, Jun; Zheng, Weihua; Xiao, Zhiyin; Yan, Yuping; Jiang, Xiujuan; Dou, Yong; Jiang, Ran; Liu, Xiaoming
Abstract : A core–shell nanoplatform was constructed with upconversion nanomaterials onto which iron carbonyl units were chemically loaded. The materials with excellent biocompatibility release CO upon irradiation with a NIR laser. Abstract : CO-release induced by near infrared (NIR) light, to which body tissues are relatively transparent, from photoactive CO-releasing molecules (PhotoCORMs) has great significance in exploring the clinical potential of CO. In this work, a novel upconversion nanoparticle-based nanoplatform, UCNPs@SiO2 -CORMs, has been developed using a one-pot reaction. The materials liberate CO under the irradiation of NIR light. TEM images of the materials showed that this nanoplatform consisted of a core–shell structure. On the surface were incorporated thiol groups through which mono-iron(ii ) carbonyl units, "Fe(η 5 -Cp)(CO)2 " were successfully anchored by a ligand exchange reaction between [Fe(η 5 -Cp)(CO)2 I] (1 ) and the thiol groups. The core of the materials consists of β-NaYF4 :Yb 3+ /Er 3+ upconversion nanoparticles (UCNPs). Strong emission bands around 530 and 550 nm from the materials upon irradiation by NIR fall into the broad band of the electronic spectrum of the materials. Consequently, the constructed nanoplatform steadily released CO upon irradiation with a 980 nm laser (1 W cm −2 ). Kinetic analysis suggests that CO-release from UCNPs@SiO2 -CORMs in DMSO/D2 O media fits a zero-order reaction model. Assessment of the cytotoxicity of UCNPs@SiO2 -CORMs indicated that they showed excellent biocompatibility and no significant photo-toxicity.